Analyzing the Interplay of Financial Inclusion, Income Inequality, and Carbon Dioxide Emissions: Evidence from Pakistan - Gardezi, Muhammad Ali; Zafar, Bakhtawar; Zaib, Aurang; Rasheed, Ayesha (iRASD Journal of Economics, 2024)
The current study uses annual time-series data from Pakistan from 1998 to 2022 to investigate the complex link between financial addition, economic inequality, and carbon emissions. The Auto-regressive Distributed Lag (ARDL) model is used in the study to look at the dynamic correlations between variables including financial addition, income inequality, and carbon emissions. The empirical data indicates that increasing financial inclusion leads to a significant reduction in CO2 emissions. In contrast, economic inequality, energy consumption, and growth have a positive correlation with CO2 emissions. These conclusions show the complicated relationship between socioeconomic determinants and environmental effects. Furthermore, the study's implications extend beyond Pakistan, giving valuable information to policymakers dealing with similar difficulties in other developing countries. This work contributes to the global discourse on sustainable growth and climate action by promoting economic addition and addressing financial disparities. It emphasizes the importance of implementing specific policy actions that promote both economic fairness and environmental sustainability. Such approaches have the potential to not only reduce carbon emissions but also encourage inclusive growth, promoting the wider aim of sustainable development in Pakistan and abroad.